2023
DOI: 10.17507/tpls.1302.28
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Directionality on Student Interpreters’ Performance in Consecutive Interpreting

Abstract: Studies showed that interpreters might differ in performance when it comes to directionality. Nevertheless, limited research has been undertaken concerning the impact of directionality on student interpreters’ performance in consecutive interpreting (CI), a type of interpreting categorised by the working mode. This study aims to investigate the relationship between directionality and performance by adopting a quantitative approach. Four student interpreters from a Chinese university were selected as samples wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Interpreters’ performance in each direction also varies based on their own bilingual proficiency, which is referred to as the “asymmetry effect” or “directionality effect” ( Chou et al, 2021 ). Empirical studies ( Darò et al, 1996 ; Mead, 2000 ; Chen, 2020 ; Chou et al, 2021 ; Lu et al, 2023 ) have confirmed the existence of the directionality effect but have not reached a consensus on which interpreting direction imposes a higher cognitive load on interpreters or yields better or worse performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpreters’ performance in each direction also varies based on their own bilingual proficiency, which is referred to as the “asymmetry effect” or “directionality effect” ( Chou et al, 2021 ). Empirical studies ( Darò et al, 1996 ; Mead, 2000 ; Chen, 2020 ; Chou et al, 2021 ; Lu et al, 2023 ) have confirmed the existence of the directionality effect but have not reached a consensus on which interpreting direction imposes a higher cognitive load on interpreters or yields better or worse performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there are still advocates for interpreting in this direction. Studies have shown that interpreting from one’s A language achieves a higher level of accuracy and completeness ( Rinne et al, 2000 ; Lu et al, 2023 ) because of the minimal mental effort required for understanding the source speech in one’s native language. This, in turn, facilitates better quality of the interpreting output ( Denissenko, 1989 ) and smooth delivery ( Chen, 2020 ).…”
Section: Literature Reviewmentioning
confidence: 99%